Implementation of omics tools for infant food microbial safety - Kalliopi Rantsiou; Dimitra Tsoureki; Cristian Botta; Jeremy Ratel; Erwan Engel; Luca Cocolin (Elsevier, 2022)
Microbial safety of infant food is a priority for food producers, regulatory authorities and consumers. Infant food is destined to a particularly sensitive section of the population that is more susceptible to foodborne diseases if compared to the general population. Preventive approaches are applied during production and commercialization that rely on the principles of Hazard Analysis Critical Control Points and on Good Hygiene Practices to guarantee food safety. Nevertheless, microbial safety hazards in infant foods still pose a public health risk. With the purpose of better understanding why and how pathogenic microorganisms contaminate infant food, an approach that integrates omics methods is here proposed and reviewed. Omics approaches are employed to study the microbial ecology of foods, to investigate the interactions of microorganisms within an ecosystem and to delineate the behavior of microorganisms during food processing.